Did humans disturb bats? Exploring the hominin-chiropter interactions in the Sierra de Atapuerca sites (early to Middle Pleistocene, Spain) - Galán, Julia (2020)
Fossil bats are common components of Pleistocene palaeontological cave-sites, sometimes appearing in levels with evidence of a human presence. As with other small vertebrates, variations observed in fossil bat palaeocommunities through a stratigraphic sequence may be correlated to palaeoclimatic and palaeoenvironmental fluctuations. As many bat species are typically cave-dwelling animals, however, the bat palaeocommunity may also be affected by hominin presence. The correlation between bat palaeocommunity dynamics and both climatic and anthropic factors is addressed in the present study by analysing their record along the Early and Middle Pleistocene sequence in the Sierra de Atapuerca. A marked deterioration in the Sierra de Atapuerca chiropter faunas occurred from 500 ka on simultaneously with a change in the occupational pattern of the predominant bat species Myotis myotis, which apparently stopped using the shelters as nursery roosts. These changes coincides with a time of extreme cold events succession during glacial periods, but also with evidence of intensive human occupation at some of the sites analysed. Some features of bat assemblages at these levels, such as differences in species composition between synchronous levels, the inability of bat palaeocommunities to recover during intermediate warmer periods, or detected seasonal alternation between hominis and humans, suggest that anthropic disturbance could have play a significant part in the decline of Middle Pleistocene bat palaeocommunities of Atapuerca.